THE ROLE OF SEAWEEDS Sargassum polycistum AND Gracilaria verrucosa ON GROWTH PERFORMANCE AND BIOMASS PRODUCTION OF TIGER SHRIMP ( Penaeous Monodon Fabr) - Munifatul Izzati (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Due to deterioration of shrimp farming environment, it is necessary to develop the technique of shrimp culture that environmentally friendly and sustainable. One of important technique to fulfill the need is integrated model with seaweeds. We investigated two different integrated model using different seaweeds species, Sargassum plagyophyllum and Gracilaria verrucosa. These two species seaweeds were cultured in tiger shrimp pond at density of 2 kg/m3. Density of tiger shrimp was 50 juvenile /m3. These experiments were conducted in 28 days. The shrimp productivity was evaluated from the rate of shrimp survival, final individual size, growth and biomass production. Seaweeds biomass production was also evaluated. Collected data was analyzed using one way ANOVA, continued by LSD test. Results indicated that the presence of both seaweeds tend to increase shrimp productivity, it was indicated by higher survival, individual size, growth rate and shrimp biomass production. The role of Gracilaria in increasing shrimp productivity was higher compared to Sargassum. It is recommended to use Gracilaria in integrated model with tiger shrimp.